Anti-Infective Agents from Plants - Bansal, Anita (My University, 2007)
Natural products are recognized by pharmaceutical industry because of their wide range biological activity. Plants have been used for medicinal purposes since time immemorial. Natural products produced by plants have been isolated as biologically active pharmacophores. Plants have been screened for their anti-infective properties as the probability of finding diverse chemistries have been implicated to serve as leads for new anti-infective drugs and using their standardized extracts as over the counter products and in the health care products. In the present study antimicrobial screening of four plants viz., Callistemon rigidus, Murraya koenigii, Atrocarpus heterophyllus & Pterocarpus esculantus, revealed the wide spectrum of antimicrobial properties of Callistemon rigidus leaves. Callistemon rigidus R.Br. is a native of Australia and is well adapted in India has been used in traditional medicine in Australia, China, Cameroon, and Asia. It rarely suffers any kind of disease. Antimicrobial activity of methanol, ethyl acetate, chloroform and acetone extract of Callistemon rigidus leaves was evaluated using Agar well diffusion assay (pre-screen) Studies revealed the activity of the different extracts against various MDR organisms both bacteria and yeast. Among the extracts tested Methanolic extract was the most active. It exhibited prominent antimicrobial activity against MRSA, VRSA, S.aureus, E.coli, E.coli O157:H7, Salmonella typhimurium, Vibrio cholerae, Streptococcus faecium, and food borne pathogens, Candida albicans and Cryptococcus neoformans. Extracts evaluated were validated against standard antibiotics e.g., Cefdinir to know the efficacy of the extracts. MIC of the extracts was determined using micro-broth dilution assay. Acetone and methanol extract exhibited similar trend of MIC against most of the test organisms and the methanol extract proved to be a potent source of leads for MRSA. The MIC of the Methanol extract was ranging between 2.70µg/µl to 0.45µg/µl for all the test bacteria. Death pattern of the test organisms in presence of the extracts was determined using microwell plates and it was found that 90-99% reduction in the microorganism count occurred between 3-9 hours after the growth. Partial purification of the extracts was done using TLC and Column chromatography. TLC bioautography was performed to determine the bioactive fractions Were showing borne pathogens, Candida albicans and Cryptococcus neoformans. Extracts evaluated were validated against standard antibiotics e.g., Cefdinir to know the efficacy of the extracts. MIC of the extracts was determined using micro-broth dilution assay. Acetone and methanol extract exhibited similar trend of MIC against most of the test organisms and the methanol extract proved to be a potent source of leads for MRSA. The MIC of the Methanol extract was ranging between 2.70µg/µl to 0.45µg/µl for all the test bacteria. Death pattern of the test organisms in presence of the extracts was determined using microwell plates and it was found that 90-99% reduction in the microorganism count occurred between 3-9 hours after the growth. Partial purification of the extracts was done using TLC and Column chromatography. TLC bioautography was performed to determine the bioactive fractions Were showingborne pathogens, Candida albicans and Cryptococcus neoformans. Extracts evaluated were validated against standard antibiotics e.g., Cefdinir to know the efficacy of the extracts. MIC of the extracts was determined using micro-broth dilution assay. Acetone and methanol extract exhibited similar trend of MIC against most of the test organisms and the methanol extract proved to be a potent source of leads for MRSA. The MIC of the Methanol extract was ranging between 2.70µg/µl to 0.45µg/µl for all the test bacteria. Death pattern of the test organisms in presence of the extracts was determined using microwell plates and it was found that 90-99% reduction in the microorganism count occurred between 3-9 hours after the growth. Partial purification of the extracts was done using TLC and Column chromatography. TLC bioautography was performed to determine the bioactive fractions Were showing antibacterial activity. The fraction 4 exhibited a very prominent anti-microbial activity against all the test organisms with largest zone of inhibition in agar well diffusion assay. Thus, the present study establishes the role of Callistemon rigidus as a medicinal plant for its use in antimicrobial herbal healthcare preparations and as a source of new drugs to MDR by Staphylococcus aureus, Candida albicans and E.coli.
Keywords: Anti Infective Agent; Antimicrobials; Agar Well Diffusion Method; TCL Bioautography